Syngap1 promotes cognitive function through regulation of cortical sensorimotor dynamics - Thomas Vaissiere; Sheldon D. Michaelson; Thomas Creson; Jessie Goins; Daniel Fürth; Diana Balazsfi; Camilo Rojas; Randall Golovin; Konstantinos Meletis; Courtney A. Miller; Daniel O’Connor; Lorenzo Fontolan; et al. (Nature Communications)
Abstract Perception, a cognitive construct, emerges through sensorimotor integration (SMI). The genetic mechanisms that shape SMI required for perception are unknown. Here, we demonstrate in mice that expression of the autism/intellectual disability gene, Syngap1, in cortical excitatory neurons is required for the formation of somatomotor networks that promote SMI-mediated perception. Cortical Syngap1 expression was necessary and sufficient for setting tactile sensitivity, sustaining tactile object exploration, and promoting tactile learning. Mice with deficient Syngap1 expression exhibited impaired neural dynamics induced by exploratory touches within a cortical-thalamic network that promotes attention and perception. Disrupted neuronal dynamics were associated with circuit-specific long-range synaptic connectivity abnormalities. Our data support a model where autonomous Syngap1 expression in cortical excitatory neurons promotes cognitive abilities through the assembly of long-range circuits that integrate temporally-overlapping sensory and motor signals, a process that promotes perception and attention. These data provide systems-level insights into the robust association between Syngap1 expression and cognitive ability.